2021
DOI: 10.1371/journal.pone.0255066
|View full text |Cite
|
Sign up to set email alerts
|

First transcriptome profiling of D. melanogaster after development in a deep underground low radiation background laboratory

Abstract: Natural background radiation is a permanent multicomponent factor. It has an influence on biological organisms, but effects of its deprivation still remain unclear. The aim of our work was to study for the first time responses of D. melanogaster to conditions of the Deep Underground Low-Background Laboratory DULB-4900 (BNO, INR, RAS, Russia) at the transcriptome level by RNA-seq profiling. Overall 77 transcripts demonstrated differential abundance between flies exposed to low and natural background radiation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 68 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have confirmed the changing patterns of various living organisms in this special deep-underground environments, including protozoa (Paramecium tetraurelia and Synechococcus lividus) (1,5), Saccharomyces cerevisiae (6), mammalian cells (V79, FD-LSC-1) (4, 7), and Drosophila melanogaster (8,9). Planel, Kawanishi, and Castillo described that cell proliferation was slowed down (5,10,11).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have confirmed the changing patterns of various living organisms in this special deep-underground environments, including protozoa (Paramecium tetraurelia and Synechococcus lividus) (1,5), Saccharomyces cerevisiae (6), mammalian cells (V79, FD-LSC-1) (4, 7), and Drosophila melanogaster (8,9). Planel, Kawanishi, and Castillo described that cell proliferation was slowed down (5,10,11).…”
Section: Introductionmentioning
confidence: 72%
“…In recent years, the study of the biological impact of deepunderground laboratories has received increasing attention from international research teams (9,25,(36)(37)(38)(39). This study attempts to reveal the potential effects related to sleep quality a DUvsG refers to the group "Deep-underground vs. ground, " GSQvsPSQ refers to the group "Good sleep quality vs. poor sleep quality".…”
Section: Discussionmentioning
confidence: 99%
“…In principle, the observed difference could also be linked to some other factors difficult to control (i.e., differences in air quality, vibrations related to nearby installations, the presence of sunlight at RRE and not at LRE, etc.) as proposed by Zarubin et al [ 7 ]. We used incubators to avoid at least some of the proposed confounding factors and tried to get more insight on the involvement of the environmental radiation on the modulation of the radiation-induced DNA damage, directly investigating the role of specific components of the environmental radiation field on the response of Drosophila larval neuroblasts [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Being among the most efficient places for experimental isolation from radiation, some DULs have become multidisciplinary sites hosting important studies in fields such as geology, geophysics, the climate, environmental, and space sciences, technology/instrumentation development, and radiobiology. So far, all biological studies carried out in DULs strongly indicate that the deprivation of natural background radiation affects, although to varied degrees, the growth and transcription profiles of bacteria as well as of unicellular and multicellular eukaryotes [ 1 , 4 , 5 , 6 , 7 ]. Moreover, several experiments indicate that cell cultures kept in this strongly reduced background show higher susceptibility to subsequent radiation-induced DNA damage than parallel cultures kept in external radiation background [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in several genes related to ribosomal proteins, membrane transport, respiration, and antioxidant regulation for increased reactive oxygen species (ROS) removal were also observed in experiments carried out inside DUL on mammalian cell cultures and organisms (Smith et al 1994 ; Fratini et al 2015 ; Van Voorhies et al 2020 ; Liu et al 2020b ; Zarubin et al 2021 ; Castillo et al 2015 ). In a recent paper, Fischietti et al ( 2020 ) reported that pKZ1 A11 mouse hybridoma cells growing underground at the LNGS display a qualitatively different response to stress; induced by over-growth with respect to the external reference laboratory.…”
Section: Experimental Evidence Of a Dose Rate Effectmentioning
confidence: 93%